Factors affecting the outcome of adenoidectomy in children treated for chronic otitis media with effusion. Issue 5 (October 2018) - Blioskas, Sarantis; Karkos, Petros; Psillas, George; Dova, Stamatia; Stavrakas, Marios; Markou, Konstantinos
Abstract: Objective: The aim of this cohort was to determine potential risk factors, concerning the effectiveness of adenoidectomy in the treatment of chronic otitis media with effusion in children. Methods: Ninety six children with chronic otitis media with effusion treated with adenoidectomy were enrolled in this study. A thorough medical history was taken, including family history of otologic disease, parental smoking habits and breast feeding history. Radiographic palatal airway size was measured preoperatively, whereas the presence of allergy was also investigated. All patients were, postoperatively, followed up for a period of two years, in three month intervals. Disease course was classified as "complete remission", "improvement" or "consistence", in every postoperative evaluation, according to strictly established criteria. Results: Children's age proved to be a significant factor in the postoperative outcome of adenoidectomy, as a treatment of chronic otitis media with effusion, especially when comparing patients being over and under the fifth year of age. Also, the presence of allergy, family history of otologic disease and palatal airway size, all proved to influence postoperative outcome in a statistical significant way (p < 0.05). On the other hand, child's sex, passive smoking, breast feeding and previous acute otitis media infections did not seem to alter the efficacy of adenoidectomy. Conclusion: Adenoidectomy remains a cornerstone in the treatment of chronic otitis media with effusion in children. Results document that young age, presence of allergy predisposition, otologic family history and small palatal airway can be important drawbacks and should be intensively sought for and taken into account, during treatment planning.